Gambaran Dermoskopi pada Kanker Kulit - Hamidah Luthfidyaningrum; Irmadita Citrashanty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Skin cancer is a lump or overgrowth of skin tissue that affects part or all of the skin layer and has an uneven structure with differentiated blood and/or lymph vessels. The diagnosis of skin cancer can be established by anamnesis, clinical examination by looking at skin efflorescence, supporting examinations such as dermoscopy, and histological examination as the gold standard. . A proper diagnosis can only be achieved through a time- consuming and laborious process of histopathological testing. Dermatoscopy or dermoscopy is a non-invasive method of observing deeper skin structures, allowing rapid diagnosis of pigmented lesions, but does not replace histological examination. This reference provides an overview of the role of dermoscopy in supporting the diagnosis of skin cancer lesions.